2011
DOI: 10.4103/0974-777x.77294
|View full text |Cite
|
Sign up to set email alerts
|

Study of susceptibility towards varicella by screening for the presence of IgG antibodies among nursing and medical students of a tertiary care teaching hospital in Pune, India

Abstract: Background:It is believed that all suffer from chickenpox infection in their childhood. Many studies abroad and some in India clearly indicate that many individuals escape the infection in childhood, and thus, remain susceptible in adulthood. Adulthood chickenpox is a more serious infection than childhood. Prior screening of health care workers for the presence of IgG antibodies against Varicella will not only prevent hospital outbreaks but also economic and academic loss faced by the students. This will also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The prevalence of prior VZV infection as demonstrated by presence of detectable VZV IgG was reported to be as high as 80–95% in young adults worldwide, and 90.2–95.8 in Israel. In IBD patients, a VZV seropositivity rate of 77% was demonstrated in a cohort of paediatric patients from Buffalo, New‐York (mean age 12 years).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of prior VZV infection as demonstrated by presence of detectable VZV IgG was reported to be as high as 80–95% in young adults worldwide, and 90.2–95.8 in Israel. In IBD patients, a VZV seropositivity rate of 77% was demonstrated in a cohort of paediatric patients from Buffalo, New‐York (mean age 12 years).…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in Mumbai, 28% of nurses were found to be seronegative for antibodies against the varicella zoster virus [ 29 ], and in another study, varicella susceptibility among medical, dental and nursing students was found to be 25.8% [ 19 ]. Similarly, a study in a tertiary care hospital in Pune, India, reported that 25.6% of the 78 nursing and medical students were susceptible to varicella infection [ 30 ]. A retrospective study conducted in a hospital in Vellore, India, revealed an annual varicella incidence rate of 0.72%, increasing to a rate of 3.22% among student nurses; serological samples taken prior to admission revealed only 29.7% of student nurses produced antibodies against the varicella zoster virus [ 31 ].…”
Section: Vpds and Their Impact On Hcps Across Indiamentioning
confidence: 99%